Corporate Governance Mechanisms with Firm Performance: A Study on Malaysia's and Hong Kong's Real Estate Investment Trust (REITs) Public Listed Companies - David, Ching Yat Ng; Yen Wen Chang; Suet Cheng Low (Center for Risk Management & Sustainability and RSF Press, 2021)
Corporate governance (CG) mechanisms might have a significant effect on firm performance (FP). The purpose of this study was to evaluate if CG mechanisms impact the FP among Malaysia's REITs (M-REITs) and Hong Kong's REITs (H-REITs). The effect of CG's variable on FP can be analyzed by using Panel data analysis. Return on Assets (ROA), Return on Equity (ROE) and Tobin's Q were employed to measure the FP. Data were collected from the annual report available on Bursa Malaysia and the Stock Exchange of Hong Kong Limited for 2010 until 2019. The finding suggests that H-REITs were more significantly affected by CG mechanisms as compared to M-REITs.